Communication Development of Preschool Children with Insufficient Development of Language System - Cupere, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article explores communication development of preschool children with insufficient development of the language system. Children who have speech and language disorders have problems with interaction between persons in society, because they have poor narrative skills. Theoretical aspect is analyzed about communication development differences in preschool children with normal language development and with insufficient development of the language system.